Development of fruit battery sensor with charging method for oil palm fruit ripeness detection - Kamal Azhar, Nisa Syakirah (2021)
The oil palm fresh fruit bunches (FFB) has different maturity grading according to MPOB guidelines. Throughout the transferring process of FFB to the mills, the reception process of the FFB might contain various type of gradings which could affect the quality of the oil production. The FFB harvest from the oil plantation might be in low quality grading, immature or rotten when inspected during mills inspection. Since the FFB received at the mills might not be matured or ripen enough due to those several factors, human inspection using eyes could not measure the ripeness content that can give inaccurate grading of the FFB to be processed. Thus, a sensor or measuring instrument that highly sensitive and reliable is needed to measure and analyse the various grading of the oil palm fruit. Based on previous research works, none of the method using the charging method to be applied to the fruit battery experiment where in this study, a fruit battery-based sensor with a charging mechanism is proposed. An oil palm fruit battery sensor is designed and fabricated with aluminium and copper electrodes to test on the oil palm fruits from the FFB. The fabrication of the sensor consisted of four different types namely single, dual, three and fourth-set terminal type. Each structure of the sensor consisted of different pairs of electrodes number and different dimension size. The experimental measurement was conducted on various samples collected on the day of the testing such as ripe, under-ripe and unripe. Parameters of load resistance RL, charging voltage, Vc, and charging time, tc are tested and compared to identify its effectiveness and the best condition in sensor sensitivity performance. The evaluation from the moisture content determination is taken to compare the values and correlation with the average load voltage, Vavg obtained. A basic mathematical expression is used to analyse the graphical result by using integration and fitting line expression to conclude the ideal parameter set for the electrochemical cell sensor. A sensitivity performance is calculated to justify the development of the different types of sensor. Ideal parameters of RL=100Ω, Vc=250V and tc=10s are chosen to test on the other sensors where the development of electrodes numbers increases the sensitivity performances. A comparison of the sensor performance with a different set of the terminal is compared to identify the ideal sensor for ripeness detection. Thus, from the test results, it was found that the fourth-set type has the highest sensitivity which is 0.586 and the sensor performance increases around 154.78% from single to the fourth-set terminal sensor type. In conclusion, the charging method improving the sensitivity of the fruit battery sensor and it is verified that the sensor can determine the ripeness of the oil palm sensor. From the data consisted different parameters value, it is assumed that it can be a reference and alternative technique to grade the oil palm FFB ripeness.